Impact of mutations in epigenetic modifiers in acute myeloid leukemia: A systematic review and meta-analysis - Al-Bulushi, Fatma; Al-Riyami, Rahma; Al-Housni, Zainab; Al-Abri, Bushra; Al-Khabori, Murtadha (Frontiers in Oncology, 2022)
This is a systematic review and meta-analysis evaluating the prognostic significance of epigenetic mutations on the overall survival (OS) in Acute Myeloid Leukemia (AML). We searched for studies evaluating epigenetic mutations in AML (up to November 2018) in PubMed, Trip database and Cochrane library. Hazard ratio (HR) of outcomes were extracted, and random-effects model was used to pool the results. A total of 10,002 citations were retrieved from the search strategy; 42 articles were identified for the meta-analysis (ASXL1 =7, TET2 = 8, DNMT3A = 12, IDH =15), with fair to good-quality studies. The pooled HR was 1.88 (95% CI: 1.49‒2.36) for ASXL1 mutation, 1.39 (95% CI: 1.18‒1.63) for TET2 mutation, 1.35 (95% CI 1.16-1.56) for DNMT3a and 1.54 (95% CI: 1.15-2.06) for IDH mutation. However, there was a substantial heterogeneity in the DNMT3a and IDH studies. In conclusion epigenetic mutations in ASXL1, TET2, DNMT3a and IDH adversely impact OS in patients with AML albeit with considerable heterogeneity and possibly publication bias. Further studies are required to address these limitations.